Numerical Simulations of GFRP-Reinforced Columns Having Polypropylene and Polyvinyl Alcohol Fibers - Liaqat Ali; Ahsan Nawaz; Yong Bai; Ali Raza; Muhammad Kashif Anwar; Syyed Adnan Raheel Shah; Syed Safdar Raza (Complexity)
The present investigation aims to propose a numerical model for assessing the complex damaging response of glass fiber-reinforced polymer- (GFRP-) reinforced concrete columns having hybrid fibers and confined with GFRP spirals (GFHF columns) under concentric and eccentric compression. Fiber-reinforced concrete (FRC) consists of polyvinyl alcohol fibers (PVA) and polypropylene fibers (PF). A total of six GFHF circular columns were constructed having a circular cross section of 250 mm and a height of 1200 mm. A commercial package ABAQUS was used for the finite element analysis (FEA) of the GFHF columns by using a modified concrete damage plastic (CDP) model for hybrid fiber-reinforced concrete (HFRC). The damaging response of GFRP bars was defined using a linear elastic model. The results depicted that the failure of GFHF columns occurred either in the upper or in the lower half portion with the rupture of GFRP longitudinal bars and GFRP spirals. The decrease in the pitch of GFRP spirals led to an improvement in the axial strength (AS) of GFHF columns. The eccentric loading caused a significant reduction in the AS of columns. The comparative study solidly substantiates the validity and applicability of the newly developed FEA models for capturing the AS of GFHF columns by considering the axial involvement of longitudinal GFRP bars and the confinement effect of transverse GFRP spirals. So, the suggested numerical model having a complex system of equations for HFRC can be used for the accurate analysis of HFRC members.